Niveles de deficiencias nutricionales en caoba (Swietenia macrophylla King) desarrollada a nivel de invernadero en el distrito de La Banda de Shilcayo - San Martín - Salas Guerra, Magna Rubi (2019)
The research work was carried out in the vegetative propagation greenhouse of the Peruvian Amazon Research Institute, located in the department and province of San Martín, Banda de Shilcayo district, Bello Horizonte - Pucayacu, which we provide a scope on the "study of nutritional deficiencies in mahogany (Swietenia macrophylla king) developed at greenhouse level in the district of the Banda de Shilcayo - San Martín", We used a Completely Random Design (DCA). Evaluating 12 treatments and one control, with four repetitions in square with the technique of missing elements. The treatments are T0 Present macro and micro nutrients (Control), T1 Nitrogen (N), T2 Phosphorus (P), T3 Potassium (K), T4 Calcium (Ca), T5 Magnesium (Mg), T6 Sulfur (S), T7 Iron (Fe), T8 Manganese (Mn), T9 Boron (B), T10 Zinc (Zn), T11 Copper (Cu) and T12 Molybdenum (Mo). Mahogany botanical seeds were used, later the substrates were prepared for the filling of storage bags in proportions of 1: 1: 1 (agricultural land, charred husk and compost). The results of our study show according to the technique of the missing element in the present study of nutritional deficiencies, iron and nitrogen treatments were identified with greater symptoms of deficiencies obtained, treatments T1, T3, T4, T5, T6, T7, T8, T9 and T12, presented a greater evidence of chlorotic symptoms in the leaves of the plants. T1 treatment showed a slow growth. The treatment T1, T2, T8 and T9 showed deficiencies of abnormal colors visible on leaves.